Changing Compliance of Poly(Vinyl Alcohol) Tubular Scaffold for Vascular Graft Applications Through Modifying Interlayer Adhesion and Crosslinking Density - Jeong, YeJin; Yao, Yuan; Mekonnen, Tizazu H.; Yim, Evelyn K. F. (Frontiers in Materials, 2021)
Poly(vinyl alcohol) (PVA) is a water-soluble polymer and forms a hydrogel that has been studied as a potential small-diameter (<6 mm) vascular graft implant. The PVA hydrogel crosslinked using sodium trimetaphosphate (STMP) has been shown to have many beneficial properties such as bioinert, low-thrombogenicity, and easy surface modification. Compared to conventional synthetic vascular graft materials, PVA has also shown to possess better mechanical properties; however, the compliance and other mechanical properties of PVA grafts have yet to be optimized compared to the native blood vessels. Mechanical compliance has been an important parameter to be studied for small-diameter vascular grafts, as compliance has been proposed to play an important role in intimal hyperplasia formation. PVA grafts are made using dip-casting a cylindrical mold into crosslinking solution. The number of dipping can be used to control the wall thickness of the resulting PVA grafts. In this study, we hypothesized that the number of dip layer and wall thickness, the chemical crosslinking, and interlayer adhesive strength could be important parameters in the fabrication process that would affect compliance. This work provides the relationship between the wall thickness, burst pressure, and compliance of PVA. Furthermore, our data showed that interlayer adhesion as well as chemical and physical crosslinking density can increase the compliance of PVA grafts.